Regular condom use tends to decrease cervical lesions in resident-commercial sex workers in Sub-Saharan Africa - Odigie, Efosa Bolaji; Achukwu, Peter Uwadiegwu (Universa Medicina, 2018)
BACKGROUNDCervical lesions are abnormalities seen in tissues and cells examined from the uterine cervix. These abnormalities are on the increase and are ignored; thereby constituting major health problems in resident commercial sex workers (CSWs) who temporarily reside in brothels for sex business. Hence, we investigated the associations between behavioural risk factors and cervical lesions in resident commercial sex workers. METHODSWe conducted a cross-sectional study among 119 resident commercial sex workers using questionnaires as the data gathering tool, liquid-based cytology for cervical lesions screening, and microscopy for examination of slides. Statistical analyses were conducted using Epi- Info™ version 6.4 and STATISTICA (StatSoft, version 5, 2009 Edition, Atlanta, GA 30329-4027 USA). Data were analysed using multivariate and simple logistic regression analyses, while the level of significance was set at p £0.05. RESULTSThe behavioural risk factors, like smoking and hard drugs, alcohol intake, commercial sex duration, client’s daily patronage and sex frequency were not significant apart, but regular condom use tends to decrease the cervical lesions in CSWs (OR=0.91;95% C.I. 0.92-1.06), including anal and oral sex (OR = 0.99 (95% C.I. 0.29-3.60). The patterns of cervical lesions further showed acute and chronic cervicitis with a prevalence of 10.1%, including low-grade squamous intraepithelial lesion (LSIL) and atypical squamous cells of undetermined significance (ASCUS). We recorded 8/12 (66.7%) for acute cervicitis, 4/12 (33.3%) chronic, and 82.4% negative. CONCLUSIONWe suggest that behavioural risk factors are associated with cervical lesions and that regular condom use tends to decrease cervical lesions among resident CSWs.